A Lipidomic Study of Phospholipid Classes and Species in Human Synovial Fluid. Issue 9 (26th August 2013) - Kosinska, Marta Krystyna; Liebisch, Gerhard; Lochnit, Guenter; Wilhelm, Jochen; Klein, Heiko; Kaesser, Ulrich; Lasczkowski, Gabriele; Rickert, Markus; Schmitz, Gerd; Steinmeyer, Juergen
<x xml:space="preserve">Abstract</x> Objective Membrane phospholipid species contribute to boundary lubrication that is provided by synovial fluid (SF). Altered levels of lubricants can be associated with increased friction, leading to articular cartilage damage. This study was undertaken to determine whether the composition of phospholipid species is altered in diseases of human knee joints. Methods The study was performed using SF from unaffected controls and patients with early osteoarthritis (OA), late OA, or rheumatoid arthritis (RA). Lipids were extracted from cell‐ and vesicle‐free SF from 9 control donors postmortem and from 17 patients with early OA, 13 patients with late OA, and 18 patients with RA. Phospholipid species were quantified by electrospray ionization tandem mass spectrometry. Results We conducted lipidomic analysis to provide the first detailed overview of phospholipid species in human SF. We identified 130 lipid species belonging to 8 lipid classes (phosphatidylcholine, lysophosphatidylcholine, phosphatidylethanolamine, plasmalogens, phosphatidylserine, phosphatidylglycerol, sphingomyelin, and ceramide). Compared to SF from controls, SF from patients with early OA and those with late OA had higher levels of most phospholipid species. Moreover, the concentrations of 64 and 27 phospholipids differed between RA and early OA SF and between RA and late OA SF, respectively. Also, the levels of 66 phospholipid species were altered in early OA versus late OA. Conclusion Our data indicate disease‐ and stage‐dependent differences in the relative composition and levels of phospholipid species in human SF. Such alterations might affect articular joint lubrication. Because certain phospholipids scavenge reactive oxygen species (ROS) and are pro‐ or antiinflammatory, any altered phospholipid level might influence ROS‐scavenging activity of SF and the inflammatory status of joints. Thus, phospholipids may be associated with the pathogenesis of OA.